Need to know : [large type] World War II and the rise of American intelligence - Reynolds, Nicholas (Nicholas E.) (Harper Large Print, an imprint of HarperCollins Publishers, 2022)
"The entire vast, modern American intelligence system--the amalgam of three-letter spy services of many stripes--can be traced back to the dire straits the world faced at the dawn of World War II. Prior to 1940, the United States had no organization to recruit spies and steal secrets or launch covert campaigns against enemies overseas and just a few codebreakers, isolated in windowless vaults. It was only through Winston Churchill's determination to mobilize the US in the fight against Hitler that the first American spy service was born, built from scratch against the background of the Second World War. In Need to Know, Nicholas Reynolds explores the birth, infancy, and adolescence of modern American intelligence. In this first-ever look across the entirety of the war effort, Reynolds combines little-known history and gripping spy stories to analyze the origins of American codebreakers and spies as well as their contributions to Allied victory, revealing how they laid the foundation for the Cold War--and beyond." --publisher's website.